Skating efficiency and technique during roller speed skate using innovative piezoelectric smart socks: an exploratory study - Bongiorno, G.; Minisini, F. G.; Biancuzzi, H.; Dal Mas, F.; Miceli, L. (Frontiers in Sports and Active Living, 2025)
This study presents an innovative system for analyzing roller speed skating techniques. It involves socks equipped with piezoelectric sensors and accelerometers, for real-time data collection and synchronization with video signal. Sensors are mixed into cotton fibers, placed in three-foot areas, while the accelerometer is positioned above the external malleolus. Using this system, connected to a mobile APP via Bluetooth, data on foot pressure points, and efficiency metrics, are acquired and calculated. Comparative analysis of a high level competitive and a novice skater highlighted the ability of the system to detect different motor patterns while skating. The high level competitive exhibited different types of strides, with different utilization of foot areas and subsequent accelerometric values. The system could identify the "digital signature" of optimal skating technique, providing training insights for beginners and improving performance tracking. Future applications include building an elite athlete database to refine movement suggestions, with potential adaptability to other cyclic sports.